2015
DOI: 10.1016/j.rser.2015.07.109
|View full text |Cite
|
Sign up to set email alerts
|

Wind speed and power characteristics for Jubail industrial city, Saudi Arabia

Abstract: Abstract:This paper presents the wind characteristics and resource assessment of the largest industrial base in the Middle East (Jubail industrial city) using measured hourly mean wind speed data at 10, 50 and 90 m above ground level (AGL) from 2008 to 2012. At respective heights, the mean wind speeds were found to be 3.34, 4.79 and 5.35 m/s. At 50 and 90 m AGL, the availability of wind speed above 3.5 m/s was more than 75%. The prevailing wind direction was from the north-west. The local wind shear exponent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…The renewable sources of energy are independent of the location and hence can be tapped anywhere, and can provide energy to people living in remote areas which are not connected to the grid. Of these clean and freely available sources of energy, wind has been accepted commercially [1][2][3] due to ease of installation, operation and maintenance, and availability of advanced wind turbines of all sizes from few kilowatts to multi-megawatt. It is easy and fast to deploy wind turbines requiring minimal attention.…”
Section: Introductionmentioning
confidence: 99%
“…The renewable sources of energy are independent of the location and hence can be tapped anywhere, and can provide energy to people living in remote areas which are not connected to the grid. Of these clean and freely available sources of energy, wind has been accepted commercially [1][2][3] due to ease of installation, operation and maintenance, and availability of advanced wind turbines of all sizes from few kilowatts to multi-megawatt. It is easy and fast to deploy wind turbines requiring minimal attention.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the authors use frequently the performance indicators on an annual basis or for periods ranging from 1 to 10 years to evaluate the wind potential of a site, but these still estimated calculations. The purpose of this simulation is to measure the power produced by each station to get an idea of the different sites in terms of energy potential.…”
Section: Resultsmentioning
confidence: 99%
“…The study concluded that under the present scenario, the wind power potential can be exploited for off-grid applications for power generation. Baseer et al [30] studied the wind power characteristics for Jubail, the industrial city of Saudi Arabia using hourly mean wind speed measured at 10, 50, and 90 meters above ground level over a period of 5 years from 2008 to 2012. The study reported that 6825 MWh of energy could be generated annually at a plant capacity factor of 25% using a wind turbine of 3 MW rated capacity.…”
Section: Saudi Arabia's Wind Power Research and Development Updatementioning
confidence: 99%